2015
DOI: 10.3109/0284186x.2015.1061214
|View full text |Cite
|
Sign up to set email alerts
|

External validation of a prognostic CT-based radiomic signature in oropharyngeal squamous cell carcinoma

Abstract: Methods. A total of 542 OPSCC patients were included for which we determined the prognostic index (PI) of the radiomic signature. We tested the signature model fit in a Cox regression and assessed model discrimination with Harrell's c-index. Kaplan-Meier survival curves between high and low signature predictions were compared with a log-rank test. Validation was performed in the complete cohort (PMH1) and in the subset of patients without (PMH2) and with (PMH3) visible CT artifacts within the delineated tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
143
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(150 citation statements)
references
References 34 publications
7
143
0
Order By: Relevance
“…This result is consistent with previously published studies investigating local control [12] and overall survival [13,15] as endpoints. To understand the underlying biological processes of these findings, it would be of great interest to investigate if radiomic features corresponding to heterogeneity correlate with histopathological stainings of cell proliferation, microvessel density or hypoxia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with previously published studies investigating local control [12] and overall survival [13,15] as endpoints. To understand the underlying biological processes of these findings, it would be of great interest to investigate if radiomic features corresponding to heterogeneity correlate with histopathological stainings of cell proliferation, microvessel density or hypoxia.…”
Section: Discussionsupporting
confidence: 93%
“…On the level of anatomical imaging, pre-treatment CT radiomics was found to be prognostic for local tumor control [12] and overall survival [11,13,14,15] in head and neck cancer, significantly stratifying patients into low-and high-risk groups. Those studies showed that tumors, which are heterogeneous in terms of CT density are associated with a worse prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In CT images, especially in the head and neck region, textural features can be affected by the presence of metal streaks due to dental fillings. 41 There is the possibility to reduce metal artefacts using some promising techniques, 42 but as texture analysis relies on extracting meaningful information from medical images, they could introduce artificial texture by modifying image information.…”
Section: Ct Imagesmentioning
confidence: 99%
“…In fact, these studies reported high values of accuracy, considering the radiomic signature estimated in a selected population and applied on an independent one from another institute, or from another body region, reporting high values of accuracy. 4,41,107 If this kind of validation is not feasible, some other evaluations should be performed, for example, using test and training sets, which should be taken from a separated cohort or at least considering leave-one-out cross-validation. 9 Even if texture analysis was carried out in the most rigorous way and if significant models that could predict tissue response to radiation or provide a characterization of tumour heterogeneity were found, the biological interpretation of these parameters remains one of the major questions about texture analysis.…”
Section: Limitations Of Texture Analysismentioning
confidence: 99%
“…Radiomics involves the extraction of additional quantitative data from medical images using advanced imaging processing and analysis tools (98). These quantitative data extend beyond what is visible to the human eye and can be powerfully correlated with patient outcomes (99,100).…”
Section: Imaging For Treatment Response Assessment After Completion Omentioning
confidence: 99%